Chemoselective Synthesis of N-Arylenaminones and 3-Aroylquinolines by Synergistic Control of Temperature and Amount of Catalyst - Zhou, Pan; Hu, Biao; Rao, Kairui; Li, Lingdan; Yang, Jiao; Gao, Chuanzhu; Wang, Fengping; Yu, Fuchao (Synlett, 2018)
An efficient and practical method has been developed for the divergent synthesis of N-arylenaminones and 3-aroylquinolines from 2-aminoaryl ketones and N,N-dimethylenaminones in the presence of 4-toluenesulfonic acid through synergistic control of the temperature and amount of catalyst. Furthermore, gram-scale synthesis and synthetic applications have been evaluated. Features of this protocol include controllable results, mild conditions, good functional-group tolerance, operational simplicity, and excellent yields.
Keywords: divergent synthesis; arylenaminones; aroylquinolines; dimethylenaminones